Gastric ulcer healing activity of Sri Lankan black tea (Camellia sinensis L.) in rats - Ratnasooriya, W.D.; Fernando, T.S.P. (My University, 2009)
This study examined the gastric ulcer healing potential of black tea (Camellia sinensis) using Sri Lankan high grown Dust grade No: 1 black tea in rat acetic acid-induced gastric ulcer model. Three oral doses (84, 167 or 501 mg/ml) of black tea brew (BTB) made according to ISO recommendations were used in the evaluation of gastric ulcer healing activity. The results showed a significant (P < 0.05) and dose-dependent gastric ulcer healing activity (in terms of reduction in gastric ulcer area). This effect had a rapid onset (with in 14 days). The gastric ulcer healing activity of BTB was however inferior (by 9 fold) to omeparazole, the reference drug. B'f B displayed in vitro antioxidant activity (using DPPH assay; by 2985-3923 Trolox equivalents ig/1), and also inhibited in vitro nitric oxide production (3-78 %). In addition, BTB had antihistamine activity (by wheal test; by 33.5%) and increased the gastric pH (from 3.3 to 5.9) and impaired the gastric acid output {by 69%). It is concluded that black tea possessed strong, oral gastric ulcer healing activity which is mediated via multiple mechanisms